The Fimbrial Gene z3276 in Enterohemorrhagic Escherichia coli O157:H7 Contributes to Bacterial Pathogenicity - Zhang, Bicheng; Sun, Xiaohan; Fan, Hongjie; He, Kongwang; Zhang, Xuehan (Frontiers in Microbiology, 2018)
Enterohemorrhagic Escherichia coli (EHEC) O157:H7 is a zoonotic pathogen of worldwide importance that causes foodborne infections in humans. It is not capable of expressing type I fimbrial because of base deletion in the fim operon. BLAST analysis shows that the open reading frame z3276, a specific genetic marker of EHEC O157:H7, encodes a sequence with high amino acid identity to other E. coli type I fimbrial, but its definitive function in EHEC O157:H7 remains unclear. We are here to report that a z3276 mutant (Δz3276) was constructed using the reference EHEC O157:H7, the mutant Δz3276 was biologically characterized, and the pathogenicity of Δz3276 was assessed in mice in comparison with the wild-type (WT) strain. Motility and biofilm formation assays revealed a smaller twitching motility zone for Δz3276 on the agar surface and significantly decreased biofilm formation by Δz3276 compared with the parental strain. The adhesion and invasion ability of Δz3276 to HEp-2 cells showed no significant change, but the invasion ability of Δz3276 to IPEC-J2 cells was attenuated. Furthermore, in the animal study, we observed shortened and lower fecal shedding among the Δz3276 mutant-infected animals compared with those infected WT strain. The data in this study indicate that this unique gene of z3276 in EHEC O157:H7 seems to play an important role in bacterial pathogenicity.